Project-based inquiry-science: An innovative learning for thinking, teaching and assessing science-physics - Nurita Apridiana Lestari; Eko Hariyono; Dwikoranto Dwikoranto; Binar Kurnia Prahani; Utama Alan Deta (Momentum: Physics Education Journal, 2022)
Project-based Inquiry Science (PjBI-Science) is one of the embodiments of innovative learning designed for students to have abilities like scientists and to experience various investigative methodologies, which include experimentation, modelling, simulation, and data analysis in the fields of earth science, life science, and physical sciences. Not only beneficial for students, but PjBI-Science also facilitates teachers to be able to design detailed learning processes and conduct assessments according to students' thinking skills and abilities, both individually and in groups. This study aims to identify the characteristics and find the benefits of implementing PjBI-Science learning. The research method used is a systematic review with a meta-aggregation method that summarizes the results of research related to PjBI-Science qualitatively. Based on the literature review results to identify the characteristics of the implementation of PjBi-Science, conclusions were obtained regarding the benefits of implementing learning. For students, it can improve the quality of abilities in the natural science field and accommodate the learning needs to optimize thinking skills, while for teachers, it can holistically provide alternative teaching styles in an innovative way and conduct an effective assessment of the activities and cognitive abilities of students.